The Examination Procedure for Clavicle Radiography with 50º Angulation at the Radiology Installation of Regional General Hospital Yogyakarta (A Case Study of Post-Orif Clavicle Fracture) - Nuraisyah, Siti Nuraisyah; Dewi, Sofie Nornalita; Nugroho, Anshor (LPPM Universitas Dhyana Pura, 2025)
The 50º clavicle radiography examination at the Radiology Installation of Yogyakarta City Hospital added a 50º cephalad Axial (AP) projection. The purpose of this study was to determine the post-ORIF radiographic examination procedure for clavicle fracture cases with a 50º angle, the resulting diagnostic information, and the reasons for using an additional 50º Axial (AP) projection. This study used a qualitative case study approach at the Radiology Installation of Yogyakarta City Hospital. The data collection methods used were observation, interviews, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the study were that the 50º clavicle radiography examination procedure at the Radiology Installation of Yogyakarta City Hospital was carried out with general patient preparation by removing metal objects, the patient positioned supine, the object position was adjusted to the mid-clavicle detector, the acromioclavicle and sternoclavicle joints were not cut. The central point was the mid-clavicle, the horizontal central ray was 50º cephalad perpendicular to the detector, and collimation was minimized. The resulting diagnostic information pays attention to the superimposed clavicle body with plates and screws, the fracture line on the clavicle, looking at the joint space in the shoulder. The reason for using the 50º projection is to obtain diagnostic information on the entire clavicle without superimposition on plates and screws, scapula, ribs, and patient follow-up assessment. The use of the 50º cephalad projection in the Radiology Installation of Yogyakarta City Hospital can provide diagnostics, especially focusing on information on the superimposed clavicle with plates and screws, and the fracture line.